Evaluation of Nutritional Content and Physical Quality of Oil Palm Frond Silage with Different of Additive and Fermentation Length - Febrina, Dewi; Hardiyanto, La Ode; Febriyanti, Rahmi; Sadarman, Sadarman; Qomariyah, Novia; Wahyono, Teguh; Adli, Danung Nur; Rahman, Rahman (Universitas Halu Oleo, 2022)
Oil palm fronds can be used as a substitute for forage but are constrained by the high content of lignin and crude fiber. Various attempts have been made to reduce the content of lignin and crude fiber, such as adding additives with different curing times. The purpose of this study was to determine the effect of additives and fermentation length on the physical quality and nutritional content of palm frond silage. Completely Randomized Design with factorial pattern (2 factors) with three replications so that there were 27 treatment units. Factor H is the additives: H1 10% of poultry manure); H2 5% of urea) and H3 10% of poultry manure + 5% of urea). N factor is fermentation length: N1, 7 days fermentation; N2, 14 days fermentation and N3, 21 days fermentation. Physical quality (texture, aroma, color, and presence of fungus) and nutritional content (crude fat, crude fiber, and crude protein) were the parameters measured in this study. The data were analyzed by analysis of variance, and if there were differences between treatments, it was continued with the Duncan Multiple Range Test. The results showed that the physical quality (aroma, presence of fungus and texture) and crude protein content were very significantly (P<0.01) influenced by the interaction between fermentation length and additives. Oil palm fronds silage which was the addition of 5% urea with a fermentation length of 7 days, gave the best results assessed from the crude protein content of 14.69%; the texture is dense, not lumpy, not slimy, crumbly (score 3.17); the aroma is not sour/not rotten (score 2.97) there are a few fungus (0.16%) are a few fun uses (0.16%) can be given as a ration for ruminants. Keywords: additives, poultry manure, oil palm fronds, nutritional content and physical quality